Development of an industrial toxic and hazardous waste management model based on end-of-pipe and industrial ecology approaches - Mohamed, Ahmad Fariz (2007)
This study attempts to evaluate the existing industrial toxic and hazardous wastes management systems in Malaysia and subsequently proposed a new model for enhancing the efficiency and sustainability of the system. This includes analyzing the trends in waste generation, industrial development, industrial production and waste recovery. Evaluation and analysis of policy and management were focused on four main sectors, namely, legislation, institutional, financial and technology (LIFT). Findings of evaluation and analysis as well as other information gathered were used to determine issues and gaps in managing wastes. Subsequently the study developed a model for a better management system based on ex-ante Industrial Ecology model for industrial toxic and hazardous waste management in Malaysia using ecosystem concept and approach within the sustainable industrial development perspective. Trend analysis has been conducted which includes the analysis of waste generation, waste recovery, industrial development and industrial output. Malaysian industry generated 4.1 million metric tons of toxic and hazardous wastes from 1994 to 2003, with an average of 418,230 metric tons per year. It appeared that the growth trend of manufacturing in terms of production index and GDP contribution had a positive correlation with waste generation prior to 1996 and after 1997. The management of wastes in Malaysia could be categorized into three activities namely, treatment and disposal, export to foreign countries, and waste recovery. The analysis of waste distribution supported the suggestion for the ecosystem approach management. This is due to the fact that increasing amounts of toxic and hazardous waste has been recovered following the adoption of waste recycling and resource efficiency initiatives. The amount of waste being recovered has doubled from 120,570 metric tons in 2000 to 250,260 metric tons in year 2003. In terms of percentage of waste recovery represented 34.99% for 2000 and 54.30% for 2003, respectively of total wastes generated with estimated value of RM 2.83 billion. Further investigation and analysis has been performed to determine the applicability of ecosystem approach for toxic and hazardous management in Malaysia. Policy and management analyses were conducted to examine the importance of the factors based on LIFT sectors. These identified factors were adopted as the main components towards the development of an ex-ante Industrial Ecology model for a better toxic and hazardous waste management in Malaysia. The model was created as an ecosystem encompassing four habitats. Each of these habitats has its own role, function and service as well as the networks between the habitats improves the ecosystem efficiency. Essentially the ex-ante model ecosystem focused on managing the flow of waste as a resource with the main target being to increase the cycle of waste to resources and to reduce the flow of resources to waste. In essence it promotes more pro-active roles by industry and business and helps to enhance their environmental image thus increasing consumer confidence in their products and therefore sales. The overall finding of the present study clearly indicates that ecosystem approach proved to be useful. The benefits include minimization of waste disposals to the environment, reduction of dependency on natural resources such as land use for disposal sites and enhancement of efficient monitoring and enforcement activity. Finally all these benefits would lead to increased benefits to government and the society in terms of achieving sustainable industrial development in Malaysia.